Antibiotic resistance and autolysin protein expression in oral bacteria under the treatment of Stevia rebaudiana extract loaded on iron oxide nanoparticles. - Omar Sadik Shalal; Alwan Al Qushawi (Microbes and Infectious Diseases, 2025)
Background: The primary cause of dental caries is the existence and activity of bacterial organisms. In the current study, the antibacterial activity of green synthesized iron nanoparticles (FeNPs) containing extracts from Stevia rebaudiana was investigated in relation to the resistant isolates. We aimed to evaluate the development of antibiotic resistance and to suppress the same with green synthesized iron nanoparticles. Methods: The bacterial resistance pattern was evaluated in 50 patients (age group 18 to 50) in this cross-sectional descriptive study; 35 of the patients were male and 15 were female. Disk diffusion and planktonic assays were used to evaluate the antibiotic resistance of bacterial isolates. Results: The green synthesized FeNPs, with a cubical and poly dispersed size range of 40-80nm. The isolates showed a high prevalence of Streptococcus spp. (33.1%), followed by Staphylococcus spp. (21.1%) and Klebsiella spp. (5.0%), with Streptococcus mutans being the predominant species. S. mutans and S. aureus showed the highest multi drug resistant (MDR) rates, while S. oralis, S. salivarius, and Klebsiella showed low resistance against multiple antimicrobial agents. The resistance patterns of S. mutans, S. aureus, and Klebsiella to FeNPs and positive control varied slightly. S. aureus showed constant resistance patterns, while Klebsiella showed slightly different resistance patterns. Positive control also showed changes at the 9th passage. We found that half of cells treated with FeNPs were lysed in 50 minutes, compared to other lytic detergents like sodium dodecyl sulphate (SDS) and triton X 100.  Conclusion: Since antibiotic resistance results in treatment failure when antibiotic therapy is required, antibiotic resistance has grown to be a serious problem. It was discovered that the artificial FeNPs controlled the isolates' autolytic and biofilm behaviours, indicating a possible therapeutic application for them in the management of dental plaque and caries.